Cholesterol esterification and atherogenic index of plasma correlate with lipoprotein size and findings on coronary angiography - Dobiásová, Milada; Frohlich, Jiri; Sedová, Michaela; Cheung, Marian C; Brown, B Greg (Journal of lipid research, 2011)
We examined the association between rate of cholesterol esterification in plasma depleted of apolipoprotein B-containing lipoproteins (FER(HDL)), atherogenic index of plasma (AIP) [(log (TG/HDL-C)], concentrations, and size of lipoproteins and changes in coronary artery stenosis in participants in the HDL-Atherosclerosis Treatment Study. A total of 160 patients was treated with simvastatin (S), niacin (N), antioxidants (A) and placebo (P) in four regimens. FER(HDL) was measured using a radioassay; the size and concentration of lipoprotein subclasses were determined by nuclear magnetic resonance spectroscopy. The S+N and S+N+A therapy decreased AIP and FER(HDL), reduced total VLDL (mostly the large and medium size particles), decreased total LDL particles (mostly the small size), and increased total HDL particles (mostly the large size). FER(HDL) and AIP correlated negatively with particle sizes of HDL and LDL, positively with VLDL particle size, and closely with each other (r = 0.729). Changes in the proportions of small and large lipoprotein particles, which were reflected by FER(HDL) and AIP, corresponded with findings on coronary angiography. Logistic regression analysis of the changes in the coronary stenosis showed that probability of progression was best explained by FER(HDL) (P = 0.005). FER(HDL) and AIP reflect the actual composition of the lipoprotein spectrum and thus predict both the cardiovascular risk and effectiveness of therapy. AIP is already available for use in clinical practice as it can be readily calculated from the routine lipid profile.
Keywords: simvastatin; Antioxidants; apolipoproteiny B; Esterification; Lipoproteins; lipoproteiny; ateroskleróza; Drug Combinations; Cholesterol; Atherosclerosis; fixní kombinace léků; koronární angiografie; Coronary Angiography; antioxidancia; velikost částic; Simvastatin; esterifikace; Humans; koronární stenóza; Niacin; Apolipoproteins B; Coronary Stenosis; niacin; Particle Size; lidé; cholesterol